Tunneling and Suture of Thoracic Epidural Catheters Decrease the Incidence of Catheter Dislodgement - Timur Sellmann; Victoria Bierfischer; Andrea Schmitz; Martin Weiss; Stefanie Rabenalt; Colin MacKenzie; Peter Kienbaum (The Scientific World Journal, 2014)
Background. Dislocation of epidural catheters (EC) is associated with early termination of regional analgesia and rare complications like epidural bleeding. We tested the hypothesis that maximum effort in fixation by tunneling and suture decreases the incidence of catheter dislocation. Methods. Patients scheduled for major surgery (n=121) were prospectively randomized in 2 groups. Thoracic EC were subcutaneously tunneled and sutured (tunneled) or fixed with adhesive tape (taped). The difference of EC length at skin surface level immediately after insertion and before removal was determined and the absolute values were averaged. Postoperative pain was evaluated by numeric rating scale twice daily and EC tips were screened microbiologically after removal. Results. Both groups did not differ with respect to treatment duration (tunneled: 109 hours ±46, taped: 97±37) and postoperative pain scores. Tunneling significantly reduced average extent (tunneled: 3 mm ±7, taped: 10±18) and incidence of clinically relevant EC dislocation (>20 mm, tunneled: 1/60, taped: 9/61). Bacterial contamination showed a tendency to be lower in patients with tunneled catheters (8/59, taped: 14/54, P=0.08). Conclusion. Thorough fixation of EC by tunneling and suturing decreases the incidence and extent of dislocation and potentially even that of bacterial contamination.